2010
DOI: 10.11613/bm.2010.011
|View full text |Cite
|
Sign up to set email alerts
|

Development of a preanalytical errors recording software

Abstract: Raz voj prog ra ma za bi lje že nje pri jea na li tič kih pog re ša ka De ve lop me nt of a prea na lyti cal er ro rs re cor di ng sof twa re Giu sep pe Lip pi*, Pat ri zia Bo nel li, Ros sa na Ros si, Mir co Bar di, Ro sa lia Aloe, Al be rta Ca leffi , En ric het ta Bo ni lau ri U.O. di Diag nos ti ca Ema toc hi mi ca, Di par ti men to di Pa to lo gia e Me di ci na di La bo ra to rio, Azien da Os pe da lie ro-U ni ver si ta ria di Par ma, Par ma, Ita ly *Cor res pon di ng aut hor: glip

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Objective and standardized mechanisms should be adopted for systematic error tracking (20), with the ultimate goal of promoting successful risk management and safety awareness. Objective and standardized mechanisms should be adopted for systematic error tracking (20), with the ultimate goal of promoting successful risk management and safety awareness.…”
Section: Discussionmentioning
confidence: 99%
“…Objective and standardized mechanisms should be adopted for systematic error tracking (20), with the ultimate goal of promoting successful risk management and safety awareness. Objective and standardized mechanisms should be adopted for systematic error tracking (20), with the ultimate goal of promoting successful risk management and safety awareness.…”
Section: Discussionmentioning
confidence: 99%
“…7 The analysis was based on data about hemolyzed specimens entered in the two years before the implementation of the new blood drawing device (i.e., 2012 and 2013) and the two years after introducing S-Monovette in manual aspiration mode (i.e. 2015 and 2016).…”
Section: Methodsmentioning
confidence: 99%
“…With this study, the authors have showed that the implementation of this very simple and absolutely free software for systematical recording of preanalytical errors is highly favorable, since it enables harmonization of incident reporting practices within the same laboratory and even across national and international laboratories (18). This is particularly noteworthy since incidents are commonly underreported in the preanalytical phase (19).…”
Section: Preanalytical Phase Studies Recently Published In Biochemia mentioning
confidence: 99%